1989
DOI: 10.1093/wjaf/4.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Root Pruning Improves the Root System Morphology of Containerized Seedlings

Abstract: Douglas-fir (Pseudotsuga menziesii var. glauca) ponderosa pine (Pinus ponderosa var. ponderosa), and western white pine (Pinus monticola) where chemically root pruned with cupric carbonate (CuCO3) during greenhouse production. The interior walls of Styroblock 4A® and Ray Leach® pine cell containers (each 66 cm³) were coated with latex paint containing CuCO3 at concentrations of 0, 30, 100, or 300 g/l. Seedlings were potted after one growing season, initiating a standard root growth potential test (Duryea 1984)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Because of the various potential combinations of containers, media, copper forms, etc., it is not surprising that studies involving copper root pruning, often with the same species, yield slightly different to very different results. For example, cupric carbonate had little effect on shoot and root biomass of Pinus ponderosa (Wenny and Woollen 1989) whereas copper hydroxide decreased root biomass and increased shoot biomass (Dumroese and Wenny 1997). For Pinus montezumae, which also forms a grass stage, copper hydroxide yielded more shoot and root biomass than the control (Aldrete et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the various potential combinations of containers, media, copper forms, etc., it is not surprising that studies involving copper root pruning, often with the same species, yield slightly different to very different results. For example, cupric carbonate had little effect on shoot and root biomass of Pinus ponderosa (Wenny and Woollen 1989) whereas copper hydroxide decreased root biomass and increased shoot biomass (Dumroese and Wenny 1997). For Pinus montezumae, which also forms a grass stage, copper hydroxide yielded more shoot and root biomass than the control (Aldrete et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Attributes associated with higher quality root systems increased in value with root pruning, including symmetry, number of radiating straight and large roots, and two measures of root cross-sectional area (CSA) growing into landscape soil. Root pruning nearly doubled the ratio of root CSA growing from the top compared to the bottom half of the root ball, which has been associated with improved anchorage on seedlings (Wenny and Woollen 1989;Dumroese and Wenny 1997). Others found root architecture and slight anchorage improvements from shaving 57 L (Weicherding et al 2007;Gilman and Weise 2012) and 246 L (Gilman 2013) root balls when landscape planting.…”
Section: Resultsmentioning
confidence: 99%
“…Storage of resources below ground is restricted by blocked translocation from entanglement of vertical structural roots (Graham and Bormann 1966;Hay and Woods 1968;Hay and Woods 1978). Producing forestry liners with horizontal roots growing from the top of the propagation container is feasible and practical (Wenny and Woollen 1989;Dumroese and Wenny 1997). For example, Chapman and Columbo (2006) showed that coating propagation containers with copper or growing in a substrate held together by fabric mesh produced herringbone root architecture that resulted in greater stability after planting, compared to containers that deflect roots vertically.…”
mentioning
confidence: 99%
“…The same authors concluded that the rootballs in containers painted on the inside with copper carbonate ( CuCO 3 ) were more densely branched than those without copper treatment. An increased root length (Wenny and Woollen, 1989) and increased number of white root tips within the rootball (Arnold and Young, 199 1) have been reported for plants grown in copper-treated containers. McDonald et al (1984b) found an increase in the number of short roots of container-grown lodgepole pine (Pinus contorta Dougl. )…”
mentioning
confidence: 88%
“…Root dry weight was not affected by the copper treatment in their study. Roots may be distributed more evenly along the sides of the copper-treated container, with less root density at the bottom compared to a nontreated container (Wenny and Woollen, 1989). This distribution pattern may enhance survival and growth after planting (Burdett et al, 1983).…”
mentioning
confidence: 99%